PENGARUH LAMA BLANCHING UAP TERHADAP KANDUNGAN KADAR β-KAROTEN, KADAR AIR, DAYA SERAP AIR, DENSITAS KAMBA DAN RENDEMEN TEPUNG UBI JALAR KUNING (Ipomea batatas L.) - Rika Wahyu Damayanti; I Komang Suwita (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
This study aims to determine the effect of the old steam blanching method on the content of β-carotene content, moisture content, absorbency, cage density and yield of yellow sweet potato flour (Ipomeabatatasl.). The yellow sweet potato processing technique with long steam blanching has a significant effect on β-carotene content, moisture content, water absorption, kamba density and yield. The highest β-carotene content was found in the 20-minute blaching treatment (1.1695 µg / g), the highest water content of yellow sweet potato flour was found at the treatment level without blanching for 20 minutes (9.66%), water absorption of sweet potato flour the highest yellow was found at the level of blanching treatment with a time of 20 minutes (2.90 g). The highest yield o. This study aims to determine the effect of the old steam blanching method on the content of β-carotene content, moisture content, absorbency, cage density and yield of yellow sweet potato flour (Ipomeabatatasl.). The yellow sweet potato processing technique with long steam blanching has a significant effect on β-carotene content, moisture content, water absorption, kamba density and yield. The highest β-carotene content was found in the 20-minute blaching treatment (1.1695 µg / g), the highest water content of yellow sweet potato flour was found at the treatment level without blanching for 20 minutes (9.66%), water absorption of sweet potato flour the highest yellow was found at the level of blanching treatment with a time of 20 minutes (2.90 g). The highest yield o